2016
DOI: 10.3109/19401736.2015.1137900
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding reveals species composition of sharks and rays in the Indian commercial fishery

Abstract: DNA barcoding was successfully used for the accurate identification of chondrichthyans in the Indian commercial marine fishery. About 528 specimens of 111 chondrichthyan species and 34 families, collected from the Indian EEZ, were barcoded for a 655 bp region of the mitochondrial gene cytochrome c oxidase subunit 1 (COI). Generally, five specimens per species were barcoded, but numbers ranged from 2 to 13. The average Kimura 2 parameter (K2P) distance separating individuals within species was 0.32%, and the av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 42 publications
3
49
0
Order By: Relevance
“…; Bineesh et al . ). All publicly available sequences were aligned with the newly generated data for each mtDNA gene separately, and the species names associated with each sequence were kept in the initial analyses.…”
Section: Methodsmentioning
confidence: 97%
“…; Bineesh et al . ). All publicly available sequences were aligned with the newly generated data for each mtDNA gene separately, and the species names associated with each sequence were kept in the initial analyses.…”
Section: Methodsmentioning
confidence: 97%
“…Based on molecular data, size and shape of the first dorsal fin, as well as denticle morphology, the small juvenile female here reported can be undoubtedly identified as C. coelolepis . The COI sequence is considered a reliable barcode marker in fish (Ward et al ., ) and has been successfully used in the past for the identification of deep‐water chondrichthyans ( e.g ., Moura et al ., ; Bineesh et al ., ; Daly‐Engel et al ., ), including both Centroscymnus species (Moura et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Methods such as protein electrophoresis [41,[44][45][46], restriction length polymorphisms (RFLPs) [39,42], PCR methods [40,[47][48][49][50][51][52][53], species identification using insertion-deletion regions (indels) [54], and the nucleotide sequencing approaches mainly focused on mitochondrial genes and commonly using the DNA barcoding methodology, such as presented by several studies [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70]. Pank et al…”
Section: Molecular Markers and Shark Species Identificationmentioning
confidence: 99%
“…Prionace glauca, Carcharhinus falciformis, Carcharhinus limbatus, Alopias pelagicus, Mustelus henlei, and Rhizoprionodon longurio) from confiscated samples provided by the Mexican Government Agency from exportation vessels at Mazatlán and Manzanillo ports. Sembiring et al [65] and Prehadi et al [66] successfully identified shark landings from Java Island, Indonesia using a molecular approach and discussed the diversity decline observed for the Indonesian sharks, while Bineesh et al [69] used the same approach identifying sharks from the Indian commercial fishery. Recently Steinke et al 2017 used a DNA barcoding approach coupled with a secondary barcoding marker, the 16S rRNA, to identify dried fins and gill plates from Canadá, China, and SriLanka, founding twelve species cited or approved to be listed by CITES, with more than half of the identified species included within the IUCN Red List categories "Endangered" and "Vulnerable".…”
Section: Molecular Markers and Shark Species Identificationmentioning
confidence: 99%